KETIMPANGAN PENDAPATAN ANTAR KABUPATEN/KOTA dan PERTUMBUHAN EKONOMI di PROPINSI JAWA TIMUR - Denny Iswanto (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2015)
This research purposes are to analyse the intra-regional disparity and economic growth In East Java's region, the potential sectors to be developed, and to classify regions and sector in East Java based on its economic growth and per capita income. Methods that being used are economic growth analysis, Location Quotient (LQ), Shift-share, Sectoral Typology, Williamson Index, Theil Index, Pearson Correllation and Kusnetz hypothesis. The number of disadvantaged area in East Java also has to be addressed, which has reached 23 regions. Intra-regional economic disparity in 2008-2012 is above 0.5 (0,4295) and continously increasing. Meanwhile, Kuznets 'U' curve, which interpret the relationship between economic growth and disparity, is proven as unapplicable in East Java (sig-2 tailed correlation 0,160 with Williamson index and 0,257 Theil index). Recommendation to minimize the intra-regional income disparity in East Java is to apply the policy to put the disadvantaged region as the priority for the development. Potential sectors which has been the main sector for each regions are is necessary to be developed with innovation and technologyDOI: 10.15408/sjie.v4i1.2293